Chemical composition and digestibility of four Mexican tropical legumes - Sosa-Montes, Eliseo; Alejos-de la Fuente, José Isidro; Pro-Martínez, Arturo; González-Cerón, Fernando; Enríquez-Quiroz, Javier Francisco; Torres-Cardona, María Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2020)
In Mexico, the nutritional properties of tropical legumes are not widely known. Therefore, the objective of the present study was to evaluate the nutritional value of Arachis pintoi, Clitoria ternatea, Macroptilium atropurpureum and Stylosanthes guianensis. Crude protein (CP), crude fiber (CF), ether extract (EE), ash (ASH), acid detergent fiber (ADF), neutral detergent fiber (NDF), crude lignin (CL), in vitro digestibility of dry matter (IVDDM) and in situ digestibility DM (DISDM). The samples were collected in the experimental plots of the National Institute of Forest, Agricultural and Livestock Research, Veracruz state, Mexico. The evaluations were carried out in the facilities of the Zootechnics Department, Autonomous University Chapingo, State of Mexico, Mexico. Each species was evaluated, with three repetitions and each repetition was considered the experimental unit, resulting in twelve observations per variable. The means were separated using the Tukey test (p< 0.05). Arachis pintoi showed the highest percentages of CP (25.2%), ASH (9.0%), IVDDM (83.2%) and ISDDM (88.0%), and the lowest values of NDF (32.8%), ADF (26.9%) and CL (5.5%). Macroptilium atropurpureum showed the lowest percentages of CP, IVDDM, IVDDM and ASH (6.4%), and the highest values of NDF (50.9%), ADF (37.6%) and CL (11.8%). The other legumes showed intermediate or low values of all variables. Therefore, based on chemical composition and, in vitro and in situ dry matter digestibility, Arachis pintoi was the species with the best nutritional value.